Intercultural Communication Ethics in the Digital Age: Challenges of Misinformation and Propaganda a Systematic Review - Firman; Syarifuddin Dollah; Sahril Nur; Nur Aeni (Indonesian TESOL Journal, 2024)
This systematic review examines the complex challenges to intercultural communication ethics posed by the proliferation of misinformation and digital propaganda. It synthesises current research on the spread and impact of these phenomena, highlighting their effects on intercultural relations and social cohesion. The review identifies gaps in existing literature, particularly regarding strategies for promoting constructive online dialogue and ethical frameworks for digital communication. Findings emphasise the importance of media and information literacy in empowering individuals to evaluate information and make informed decisions. The review also explores the ethical considerations surrounding the use of AI in marketing and recommends educational interventions focused on multiculturalism and the dynamics of privilege. The conclusion calls for active engagement with ethical experts to safeguard social media users, enhance trust in research, and foster intercultural competence to combat misinformation and promote responsible online engagement.